Temperature analysis of steel box girder considering actual wind field. (1st November 2021) - Huang, Xu; Zhu, Jin; Li, Yong-le
Highlights: A novel thermal analysis methodology is proposed to predict the temperature distribution of steel box girders considering the actual wind field. The convection coefficient is computed based on the wind speed at the thermal boundary layer thickness through the CFD simulation. Effects of the various factors affecting the resultant temperature characteristics are quantified. Abstract: Most existing studies on bridge thermal analysis have ignored the influence of wind on the resultant temperature distribution, in which a constant value of wind speed is applied to all structural surfaces. In fact, the wind blowing across the girder exterior surface significantly affects the heat-transfer convection coefficient and consequently influences the accuracy of the thermal analysis results. For the streamlined steel box girder in particular, the local wind speeds on different surfaces even under the same inflow wind speed could vary significantly, because the steel box girder is composed of multiple surfaces with different azimuth angles. In this paper, a novel thermal analysis methodology for predicting the temperature characteristics of steel box girders is proposed considering the actual wind field distribution around the girder. Validation studies are first performed to validate the applicability of the proposed methodology. Subsequently, the proposed thermal analysis methodology is applied to a typical bridge, with which the temperature distribution characteristics of its steel box girder is investigated in detail. Meanwhile, parametric analysis, including the inflow wind speed, the season, the geometry of box girder, and the influence of vehicle are conducted to identify their effects on the temperature distribution characteristics of the girder quantificationally.